2010
DOI: 10.1590/s1808-86942010000400019
|View full text |Cite
|
Sign up to set email alerts
|

Achados audiológicos em pacientes tratados com radioterapia para tumores de cabeça e pescoço

Abstract: Radiotherapy has been widely used given its increase in the successful outcomes and cure of some cancers. Aim To evaluate the functionality of the auditory system in patients who underwent radiotherapy treatment for head and neck tumors. Materials and Methods From May 2007 to May 2008, otorhinolaryngological and audiological evaluation (Pure Tone Audiometry (air and bone conduction), Speech Audiometry, Tympanometry, Acoustic Reflex testing and Distortion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Paulino et al, 23 Johannesen et al, 24 Low et al, 8 and Dell’Aringa et al 9 reported that doses between 4000 and 6000 cGy were risk dosages for hearing loss, and suggested audiological monitoring. Treatment with Rxt in head and neck tumors can cause other ear disorders such as otitis externa, serous otitis media, 25 necrosis of the external auditory canal, and osteoradionecrosis of the temporal bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paulino et al, 23 Johannesen et al, 24 Low et al, 8 and Dell’Aringa et al 9 reported that doses between 4000 and 6000 cGy were risk dosages for hearing loss, and suggested audiological monitoring. Treatment with Rxt in head and neck tumors can cause other ear disorders such as otitis externa, serous otitis media, 25 necrosis of the external auditory canal, and osteoradionecrosis of the temporal bone.…”
Section: Discussionmentioning
confidence: 99%
“…The variable “radiation reaching the auditory system” was categorized as: no Rxt, Rxt ≤ 4000 cGy, and Rxt > 4000 cGy. 9 , 14 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation